Sociodemographic and Health Characteristics as Influencing Factors of Adolescent Marriage: A Cluster Analysis - Sulistyorini, Yuly; Wibowo, Arief; Indriani, Diah; Puspitasari, Nunik; Hariastuti, Iswari (Journal of Population and Social Studies [JPSS], 2025)
Adolescent marriage, for those under 20 years old, in Indonesia is mainly due to early pregnancy. In Malang Regency, adolescent marriage has led to a high fertility rate among women aged 15–19 years old, reaching 46.3 births per 1,000 women in 2020. This study aims to create cluster areas with the highest incidence of female adolescent marriage based on similarities in sociodemographic and health characteristics. This study used a cross-sectional approach using data from the Central Statistics Agency (BPS), the Ministry of Religious Affairs, and Religious Courts, covering 33 subdistricts with 378 villages in Malang Regency, Indonesia. Sociodemographic and health characteristics were analyzed using a k-means cluster and analysis of variance utilizing ANOVA. Cluster maps were generated using the quantum geographic information system (QGIS) application. The clusters were divided into three groups. The results showed that the sociodemographic characteristics, including youth organization and rice assistance programs, and health characteristics, including the number of hospitals, community health centers, and health clinics, were the key indicators of cluster formation. The highest incidence of female adolescent marriage was observed in Cluster 2 (mountainous areas), followed by Cluster 3 (rural areas), while Cluster 1 (urban areas) had the lowest incidence.